The Impact of Competence, Planning, and Financial Reporting on Village Fund Management through SOP as an Intervening Variable - Widodo, Agung; Supardi, Supardi; Setiyono, Wisnu Panggah (International Journal of Economics Development Research (IJEDR), 2024)
The study focuses on the impact of competence, planning, and financial reporting on village fund management, with Standard Operating Procedures (SOP) acting as a mediating variable. The aim of this research is to determine the extent to which these variables influence the effectiveness of village fund management, which plays a critical role in promoting regional development. A quantitative approach using the SEM-PLS method was employed to analyze the impact of competence, planning, and financial reporting on village fund management across four districts in Sidoarjo Regency, with SOP as an intervening variable. The results show a positive and significant relationship between Village Apparatus Competence, Village Fund Planning, and Village Financial Reporting on Village Fund Management, both directly and through the mediation of SOP. When these three factors interact, they have a strong impact, with a path coefficient of 0.619 and a T-statistics value of 3.485. SOP plays a crucial role as an intervening variable, with an indirect effect of 0.355 and a direct effect of 0.782. This model explains 68.2% of the variation in Village Fund Management, with a Goodness of Fit value of 0.640. The study highlights the importance of improving competence, planning, reporting, and SOP to enhance financial governance.